Measurements of heated rectangular jet - Chia, Gare Rern. (2013)
This project investigates the characteristics of a rectangular jet flow. The jet nozzle has an aspect ratio of 20, and expends a jet flow with velocity of 25 m/s. Hot wire anemometry was used to measure and determine the velocity of the flow at varying distances. This was done in 2 phases. The first phase involved the use of a single hot wire probe, with which the axial velocity profiles were measured. The second phase involved the use of a cross wire probe, with which both axial and lateral velocities were measured.